Controllable Lewis Base Catalyzed Michael Addition of α-Aminonitriles to Activated Alkenes: Facile Synthesis of Functionalized γ-Amino Acid Esters and γ-Lactams - He, Ze-Ying; Jang, Ho-Chol; Teng, Le-Sheng; Wei, Zhong-Lin; Liao, Wei-Wei (Synthesis, 2021)
A novel protocol for the synthesis of functionalized γ-amino acid esters and γ-lactams through a controllable Lewis base catalyzed Michael addition of α-aminonitriles to simple activated alkenes has been developed. The scope, versatility, and efficiency of the process were demonstrated.
Keywords: Lewis base; catalysis; Michael addition; α-amino nitriles; γ-amino acid derivatives